2007
DOI: 10.1007/s10044-007-0096-4
|View full text |Cite
|
Sign up to set email alerts
|

The aspect Bernoulli model: multiple causes of presences and absences

Abstract: We present a probabilistic multiple cause model for the analysis of binary (0-1) data. A distinctive feature of the aspect Bernoulli (AB) model is its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…In the case of MAP, we should expect to see a peak for the optimal value of K, indicating that relevant documents are ranked higher. Furthermore, previous work has suggested that the optimum number of topics will be close to the cardinality of the concepts underlying the data [4,11,12]. In Fig.…”
Section: Document Rankingmentioning
confidence: 91%
See 2 more Smart Citations
“…In the case of MAP, we should expect to see a peak for the optimal value of K, indicating that relevant documents are ranked higher. Furthermore, previous work has suggested that the optimum number of topics will be close to the cardinality of the concepts underlying the data [4,11,12]. In Fig.…”
Section: Document Rankingmentioning
confidence: 91%
“…The PLSA algorithm was written by Peter Gehler. 4 Convergence for PLSA was satisfied after 500 EM iterations or when the log-likelihood change was less than 1e-4. For LDA, following a preliminary experiment, we set the Dirichlet priors to α = 0.1 and β = 0.01 and the number of Gibbs sampling iterations to 1000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods using normal algebra [19] or probabilistic modeling [2,18], for example, have been proposed. The characteristics and behaviour of such methods are very different to Boolean matrix factorization, though.…”
Section: Related Workmentioning
confidence: 99%
“…Methods using normal algebra [13] or probabilistic modeling [14], [15], for example, have been proposed. The characteristics and behaviour of such methods are very different to Boolean matrix factorization, though.…”
Section: Related Workmentioning
confidence: 99%